Analisis Pemidanaan Anak Pelaku Kekerasan Seksual dalam Putusan Pengadilan Negeri Samarinda Nomor 26/Pid.Sus-Anak/2023/PN SM - Hoirul Amin; Ihwanul Muslim; Muhammad Nurcholis Alhadi (Jurnal Ragam Pengabdian, 2026)
Sexual violence involving children constitutes one of the most complex criminal law issues in contemporary legal systems because it simultaneously concerns criminal liability, victim protection, rehabilitation policy, and judicial proportionality within one legal framework. This study examines Samarinda District Court Decision Number 26/Pid.Sus-Anak/2023/PN Smr using normative legal research through statutory, case, and conceptual approaches. The statutory approach is directed at Law Number 12 of 2022 concerning Sexual Violence Crimes, Law Number 11 of 2012 concerning Juvenile Criminal Justice System, and child protection regulations. The findings demonstrate that the panel of judges applied Article 6 letter b in conjunction with Article 15 letter g of Law Number 12 of 2022 by imposing ten months of imprisonment in a juvenile correctional institution and two months of vocational training. Although the sanction formally reflects juvenile justice principles, judicial reasoning still indicates transitional inconsistency because some legal considerations remain influenced by earlier child protection norms. The novelty of this study lies in integrating  maqāṣid al-syarī‘ah as an evaluative framework for assessing modern judicial punishment, particularly through the dimensions of  ḥifẓ al-nafs, ḥifẓ al-'ird, and ḥifẓ al-nasl